Demographic and psychological predictors of grade point average (GPA) in North-Norway: a particular analysis of cognitive/school-related and literacy problems. Issue 10 (25th November 2016) - Sæle, Rannveig Grøm; Sørlie, Tore; Nergård-Nilssen, Trude; Ottosen, Karl-Ottar; Goll, Charlotte Bjørnskov; Friborg, Oddgeir
Abstract : Approximately 30% of students drop out from Norwegian upper secondary schools. Academic achievement, as indexed by grade point average (GPA), is one of the strongest predictors of dropout. The present study aimed to examine the role of cognitive, school-related and affective/psychological predictors of GPA. In addition, we examined the psychometric properties of a new scale for literacy problems (LP), as well as its role for GPA. Analyses showed that the scale had favourable psychometric properties. Multivariable regression analyses showed that study track choice, task solving skills, gender, lack of educational plans and LP predicted GPA in descending order. The major implication of the study was that GPA is related to a multiple number of demographic, cognitive and psychosocial factors, and that any interventions addressing GPA will be less effective if not addressing psychosocial in addition to cognitive/school-related factors.